Predictive Performance of Pre-service Teachers’ Teaching Techniques in Osun State University - Odekeye, Ola Tokunbo; Fakokunde, Jubril Busuyi; Alaba, Adebola Oladiji; Iwintolu, Rukayat Oyebola (Unib Press, 2024)
The study compared pre-service teachers’ scores in micro-teaching and teaching practice for three sessions ranging from 2019/2020 to 2021/2022 academic sessions for micro-teaching and 2020/2021 to 2022/2023 academic sessions for teaching practice. The study is an ex-post facto research design because it used the existing data of students’ scores in micro-teaching and teaching practice in the concerned sessions. Four hundred and thirteen (413) pre-service teachers were involved. Data were analysed using frequency count, percentage and correlation analysis. The results showed that students performed well in both micro-teaching and teaching practice with that of micro-teaching on the higher side. It also revealed a positive relationship between pre-service teachers’ performance in micro-teaching and teaching practice across the sessions. The study therefore recommends that teaching exercise should be given more attention in the training of teachers by teacher training institutions while appropriate mechanisms should be designed to attend to the shortcomings realised by pre-service teachers’ supervisors during the teaching practice exercise.